Influence of dietary supplementation of modified tall oil and vitamin E on pork chop quality, display color stability, warner-bratzler shear, and sensory panel traits - A T Waylan; P R O'Quinn; J C Woodworth; S I Koo; John A Unruh; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1999)
Seventy-two crossbred (PIC) barrows were used to determine the influence of feeding modified tall oil (MTO, 0 or .5% of diet) and vitamin E (0, 10, or 50 IU/lb of feed) on display color stability, Warner-Bratzler shear, and sensory panel traits of pork chops. Feeding MTO in combination with high levels of vitamin E to pigs during both the growing and finishing phases improved display color stability and delayed lipid oxidation of the pork loin chops without affecting tenderness and sensory evaluations. Therefore, feeding swine MTO (.5%) with high levels of vitamin E (50 IU/lb of feed) can increase the shelf-life stability of pork and potentially reduce monetary losses from deteriorated product.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Modified tall oil; Vitamin E; Pork chop